2022
DOI: 10.3390/app12042102
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Magnetoelectric Effect at Low Frequencies in Layered Polymeric Cantilevers Containing a Magnetoactive Elastomer

Abstract: In this work, the resonance enhancement of magnetoelectric (ME) coupling at the two lowest bending resonance frequencies was investigated in layered cantilever structures comprising a magnetoactive elastomer (MAE) slab and a commercially available piezoelectric polymer multilayer. A cantilever was fixed at one end in the horizontal plane and the magnetic field was applied horizontally. Five composite structures, each containing an MAE layer of different thicknesses from 0.85 to 4 mm, were fabricated. The funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…The output signal (generated voltage or charge) and the applied magnetic field strength were recorded. Since MAEs exhibit hysteretic behavior of measured quantities with respect to the applied magnetic field [ 24 , 25 , 34 , 35 ], the response to each period of an applied magnetic field is somewhat different. A hysteresis in MAEs is commonly attributed to the magnetic-field-induced restructuring of filler particles, which is also the origin of magnetic hysteresis in such a material.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The output signal (generated voltage or charge) and the applied magnetic field strength were recorded. Since MAEs exhibit hysteretic behavior of measured quantities with respect to the applied magnetic field [ 24 , 25 , 34 , 35 ], the response to each period of an applied magnetic field is somewhat different. A hysteresis in MAEs is commonly attributed to the magnetic-field-induced restructuring of filler particles, which is also the origin of magnetic hysteresis in such a material.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding resonance frequency in the absence of a magnetic field was low ( Hz). The first results [ 16 , 24 , 25 ], obtained on multiferroic layered structures containing an MAE layer and a PE polymer, confirmed that these heterostructures are promising for the development of magnetic field sensors and energy harvesting devices. It seems that contrary to the conventional paradigm, the T-T configuration leads to a higher ME voltage coefficient than the L-T configuration.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations